Charge Carrier Transport and Photogeneration in P3HT:PCBM Photovoltaic Blends. Issue 11 (3rd May 2015) - Laquai, Frédéric; Andrienko, Denis; Mauer, Ralf; Blom, Paul W. M.; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> This article reviews the charge transport and photogeneration in bulk‐heterojunction solar cells made from blend films of regioregular poly(3‐hexylthiophene) (RR‐P3HT) and methanofullerene (PCBM). The charge transport, specifically the hole mobility in the RR‐P3HT phase of the polymer:fullerene photovoltaic blend, is dramatically affected by thermal annealing. The hole mobility increases more than three orders of magnitude and reaches a value of up to 2 × 10−4 cm2 V−1 s−1 after the thermal annealing process as a result of an improved semi‐crystallinity of the film. This significant increase of the hole mobility balances the electron and hole mobilities in a photovoltaic blend in turn reducing space‐charge formation, and this is the most important factor for the strong enhancement of the photovoltaic efficiency compared to an as cast, that is, non‐annealed device. In fact, the balanced charge carrier mobility in RR‐P3HT:PCBM blends in combination with a field‐ and temperature‐independent charge carrier generation and greatly reduced non‐geminate recombination explains the large quantum efficiencies measured in P3HT:PCBM photovoltaic devices.